Motif design of Rumah Demang Abdul Ghani / Nurulain Mohamad Mukhri - Mohamad Mukhri, Nurulain (2018)
The purpose of this research is to focus on motif design of the traditional houses in Melaka. In research, I have choose Rumah Demang Abdul Ghani as a sample of the traditional house in Melaka. The building was very significant because of its historical value starting from the year that it was first built by Demang Abdul Ghani on 1894 and now it has been converted to Gellery of Demang Abdul Ghani. There are three generation of the village headman had believed inhabited this house which are Penghulu Abdul Majid, Penghulu Abdul Ghani, and Penghulu Natar. This traditional house was renovated by Jabatan Warisan Negara in 2007. Next, on 2011, this house has been a gallery to give a chance for local tourists as well as foreign tourists to visit the uniqueness and privilege of this house. The uniqueness of this traditional house was built without using a nails. Rumah Demang Abdul Ghani had been selected as subject for studies because the structure of this building represented the characteristics of malay traditional house. In the other hand, the uniqueness of this malay traditional architecture had developed by the process assimilation and alculturation. Findings show that motif designs found at this particular of house is heavily influenced by several factors in terms of cultural which will be discussed further in this paper.